Vol. 82 : Thermophysical Basis of Energy Technologies: Proceedings of the Conference, October 15-17, 2014, Tomsk, Russia; European Physical Journal Web of Conferences (EPJ Web of Conferences) - Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Zhdanova A. O. Alena Olegovna; Bulba E. E. Elena Evgenievna (2015, 2015)
Title screen